EVALUASI PENGGUNAAN TERAPI ANTIHIPERTENSI PADA PASIEN GAGAL GINJAL KRONIK DENGAN HEMODIALISIS - Nadia Husna; Niken Larasati (MEDIA ILMU KESEHATAN, 2019)
Background: End Stage Renal Disease (ESRD) occurs when Glomerular Filtration Rate (GFR) falls below 15 ml/minute/1.73m2. This condition leads to Renal Replacement Therapy (RRT) intervention namely dialysis and kidney transplantation. The intervention inclines morbidity and hospitalization rate which means more physical and financial burden to patients as the consequences. One of the physical side effects that becomes a major cause of increasing cardiovasculer mortality is hypertension. Objective: The purpose of this study was to analyze the rationale of antihypertensive therapy in haemodialysis patients. Methods: A descriptive, purposive, non experimental study gathering medical records of 97 hemodialysis with antihypertensive therapy patients of PKU Muhammadiyah Gamping hospital who were admitted from June until August 2018 was held in this study. Results: Majority of patients were female (63,92%), aged between 41-75 years (83,50%), and diagnosed with chronic kidney disease (CKD) (95,58%), received three combination of antihypertensive drugs (38,14%) using Calcium Channel Blocker namely amlodipin (20,86%). The analysis of antihypertensive therapy including accurate drugs, patients, and dosage were 83,51%, 100%, and 97,72% respectively. Conclusion: The use of antihypertensive drugs in CKD patient in PKU Muhammadiyah Gamping was approprite Keywords: Antihypertension, chronic kidney disease, evaluation, hemodialysis, hospital.